Estetyzacja epistemologiczna a modele symulacyjne - w kontekście modelu anatomicznego "Visible Human Project" - Barański, Jarosław (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2005)
Epistemological esthetization of knowledge can have a lot of forms. In this article I focus my reflection on the person that is an electronic simulation model. The background for the reflections will be the simulation anatomical model Visible Human Project (VHP). The problem is what cognitive function the model fulfils and what it simulates. Conclusions: 1. VHP is not associated with real body, but with other anatomical models; it is not a simulation of real body, but only a simulation of its perception by us; 2. The function of anatomical simulation model has educational character. It also involves projecting medical intervention, which minimalizes invasiveness of actions. It is a part of training preparing to undertake computer-aided surgical procedures.